Isytiqāq in an al-Jazeera.net Report: Ibn Jinni’s Perspective - Roudathul Aisyah; Mohammad Pribadi (Middle Eastern Culture & Religion Issues, 2026)
This study reviews the forms of isytiqāq in Arabic-language news articles on the Al-Jazeera website and analyzes the resulting semantic relationships, particularly within the framework of Ibn Jinni’s theory. This study is a library research project using primary data consisting of news articles on the Palestinian conflict and the Iran-U.S. conflict published on November 14, 2024, and April 13, 2026. The method employed is content analysis through the stages of identification, classification, and description of the forms of isytiqāq in the news texts. The results of the study indicate that two types of isytiqāq were found in the news texts: isytiqāq ṣagir and isytiqāq kabīr. Isytiqāq ṣagir appears in morphological forms such as plurals, verb conjugations, and the mazīd form, which serve to clarify the time, quantity, and dynamics of events in the news. Furthermore, isytiqāq kabīr is identified through phonemic similarities with variations in letter arrangement. The semantic relationships identified in the data from this study reveal a variety of connections, ranging from lexical relationships—which can still be traced through similarities in phonemic elements—to conceptual and contextual relationships formed by the use of words in discourse. These findings demonstrate the relevance of Ibn Jinni’s theory in modern linguistic analysis, particularly for understanding the various forms of semantic relationships that emerge in news texts.